Shoulder Dysfunction in Breast Cancer Survivors: Can Treatment Type or Musculoskeletal Factors Identify Those at Higher Risk?. Issue 3 (2nd July 2021) - Lang, Angelica E.; Murphy, Maybelle; Dickerson, Clark R.; Stavness, Ian; Kim, Soo Y.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Objective: Breast cancer is the most commonly diagnosed cancer in Canadian women. Breast cancer survivors are known to experience shoulder dysfunction, but the influence of musculoskeletal and treatment factors has yet to be investigated in a Saskatchewan population, which was the purpose of this study. Methods: Two study designs were used to assess risk factors for dysfunction: (1) a cross-sectional Web-based questionnaire and (2) prospective cohort analysis of preoperative musculoskeletal assessment combined with postoperative Shoulder Pain and Disability Index (SPADI) score. Data from the survey were summarized and analyzed using χ 2 tests ( P < .05), while nonparametric measures were used to calculate temporal differences and associations between musculoskeletal risk factors and disability. Results: Commonly reported shoulder problems after treatment were stiffness (63.5%), restricted range of motion (61.9%), and changes in arm/hand sensation (61.9%). Axillary lymph node dissection and radiation therapy were associated with more shoulder problems than other treatment types. SPADI scores increased by an average of 8.1% from baseline to 3 months postsurgery. A clinically significant 18% increase between these time points was moderately associated with a history of shoulder problems and restricted humeral extension preoperatively (average = 37.7° vs 48.9°). Conclusions: Breast cancer survivors from Saskatchewan have a high prevalence of shoulder problems following treatment. Clinically significant impairments in shoulder function are associated with select treatment types and preoperative impairments. These results can be used to identify high-risk patients before cancer treatment and direct their rehabilitation.